2015
DOI: 10.1002/sec.1314
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and ultralightweight RFID mutual authentication protocol with cache in the reader for IoT in 5G

Abstract: As one of the core techniques in 5G, the Internet of Things is more interested than ever. Furthermore, radio frequency identification (RFID) plays a crucial role in Internet of Things development. Although the low-cost RFID system has wide prospect, it has to face with huge challenges because of potential security risks, privacy problems, and efficiency because of its restrictions on processing, storage, and power in RFID tags. One of the possible solutions in secure authentication of the low-cost RFID system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 14 publications
0
51
0
2
Order By: Relevance
“…We specify the security features comparison of the improved protocol and some other related protocols in Table . Indeed, it can be observed that the improved protocol satisfies and meets the security requirements (except existential untraceability ) and is more secure and efficient than the most recent related protocols . Basically, all the protocols using pseudonym technique avoid the linear search for each tag authentication in DB but they are existentially untraceable.…”
Section: Security Analysis Of the Improved Protocolmentioning
confidence: 93%
See 1 more Smart Citation
“…We specify the security features comparison of the improved protocol and some other related protocols in Table . Indeed, it can be observed that the improved protocol satisfies and meets the security requirements (except existential untraceability ) and is more secure and efficient than the most recent related protocols . Basically, all the protocols using pseudonym technique avoid the linear search for each tag authentication in DB but they are existentially untraceable.…”
Section: Security Analysis Of the Improved Protocolmentioning
confidence: 93%
“…Let us focus only on the most recent contributions based on Chebyshev chaotic map polynomials for RFID, because of the significant number of existing protocols in several others spheres of activities . Hence, numerous chaos‐based cryptosystems have been proposed in the literature in different areas such as RFID, smart cards, and security networks . In 2013, Cheng et al proposed the RFID authentication security mechanism based on chaotic maps .…”
Section: Introductionmentioning
confidence: 99%
“…NFC is a development and breakthrough of the RFID (Radio Frequency Identification) [4][5][6] technology. It is a short-range, high-frequency, noncontact automatic identification wireless communication technology using the 13.56 MHz frequency band at a distance of less than 10 cm.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, scholars have proposed many different RFID security authentication schemes such as Hash-lock protocol [3], random Hash-lock protocol [4], Hash-chain protocol [5], lightweight and ultralightweight RFID mutual authentication protocol [6], the change of ID protocol based on hash algorithm [7], David's digital library protocol [8], distributed challenge-response authentication protocol [9] and LD authentication protocol [10], etc. However, neither do these schemes achieve a high level of security to resist a variety of attacks, nor do these protocols take into account the efficiency.…”
Section: Introductionmentioning
confidence: 99%